PENGARUH PEMBELANJAAN PERIKLANAN DAN PROMOSI HARGA PADA EKUITAS MEREK - Killa, Maklon Felipus (Journal of Indonesian Economy and Business, 2008)
This study aimed to examine the effect of perceived advertising spending and priceÂ deal on brand equityâs dimension, and the effect of brand equityâs dimension onbrand equity based on consumerâs perspective. University students in YogyakartaÂ were taken for the sample, those who owned and used notebook. Meanwhile thepurposive sampling was used for sampling technique. 350 questionnaires wereÂ distributed and 328 were used. The finding showed that brand loyalty was positivelyand significantly affected on brand equity, whereas perceived quality, brandÂ awareness, and brand image were not positively and significantly affected on brandequity. Besides, perceived advertising spending was positively and significantlyÂ affected the dimension of brand equity (perceived quality, brand loyalty, brandawareness, and brand image). Price deal was negatively and significantly affected onÂ perceived quality and brand image.Keywords: Brand equity, perceived quality, brand loyalty, brand awareness, brandÂ image, perceived advertising spending, price dealsÂ